2017
DOI: 10.4062/biomolther.2015.180
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotection of Dexmedetomidine against Cerebral Ischemia-Reperfusion Injury in Rats: Involved in Inhibition of NF-κB and Inflammation Response

Abstract: Dexmedetomidine is an α2-adrenergic receptor agonist that exhibits a protective effect on ischemia-reperfusion injury of the heart, kidney, and other organs. In the present study, we examined the neuroprotective action and potential mechanisms of dexmedetomidine against ischemia-reperfusion induced cerebral injury. Transient focal cerebral ischemia-reperfusion injury was induced in Sprague-Dawley rats by middle cerebral artery occlusion. After the ischemic insult, animals then received intravenous dexmedetomid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…After ischemia, blood reperfusion involved in the ischemic region leads to more severe damage and malfunctions in the tissues and is a major cause of cerebral ischemiareperfusion (I/R) injury. 1 Reperfusion may reduce infarction volume while improving patients' conditions initially, however reperfusion occurring after a long period of ischemia is likely to be the cause of a higher infarction volume and in turn aggravate the initial injury. 2 The Qing Shu, Hua Fan, and Shi-Jun Li authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…After ischemia, blood reperfusion involved in the ischemic region leads to more severe damage and malfunctions in the tissues and is a major cause of cerebral ischemiareperfusion (I/R) injury. 1 Reperfusion may reduce infarction volume while improving patients' conditions initially, however reperfusion occurring after a long period of ischemia is likely to be the cause of a higher infarction volume and in turn aggravate the initial injury. 2 The Qing Shu, Hua Fan, and Shi-Jun Li authors contributed equally.…”
Section: Introductionmentioning
confidence: 99%
“…Renal IRI up‐regulated the expression of TNF‐α, IL‐1β, ICAM‐1, HMGB1 and TLR4, which were alleviated by the treatment with Dex . It was also reported that Dex reduced focal cerebral ischaemia‐reperfusion injury in rats by inhibiting the expression and release of inflammatory cytokines and mediators as well as oxidative products . In an animal model of spinal cord ischaemia‐reperfusion injury, the numbers of proinflammation cytokines of the Dex group were decreased, whereas anti‐inflammation cytokines increased .…”
Section: Discussionmentioning
confidence: 95%
“…An increase of the mRNA level of the gene for INOS, encoding an enzyme for the synthesis of NO, also participating in the development of the inflammatory response in the lesion, was also noted [22,25]. In the ischemia-reperfusion model, it was also shown that cytokines (IL-1β, IL6), adhesion molecules (ICAM1, E-selectin, MMP-9), MAPK kinase, and c-fos transcription factors were involved in the development of inflammation [17,20,23,[26][27][28][29]. Wang et al studied the molecular mechanism of ischemia-reperfusion pathogenesis using genome-wide transcriptome analysis (RNA-Seq) in the hippocampus of rats at 24 h after tMCAO.…”
Section: Transcriptomics Of Ischemic Strokementioning
confidence: 94%
“…In particular, activation of the transcription factor Nf-κb was shown. An increase of the mRNA level of Cox2, which encodes one of the key enzymes for the synthesis of the pro-inflammatory prostaglandin E2 (PGE2), was accompanied by an increase in the level of the corresponding protein, not only at the source but also in adjacent regions, and accompanied by increased concentration of PGE2 [20][21][22]. At the same time, as a result of the opening of the blood-brain barrier in brain sections, extensive leucocyte infiltration was observed [21,23,24].…”
Section: Transcriptomics Of Ischemic Strokementioning
confidence: 99%